Biochemical parameters of Nile tilapia exposed to thiamethoxam (Research, Society and Development, 2020)
Thiamethoxam is an insecticide in the class of neonicotinoids and although it has been on the market for more than 20 years, there are still few studies regarding its toxicity to fish. The objective of this work was to evaluate the toxicity of a thiamethoxam-based insecticide to Nile tilapia exposed to a sublethal concentration by means of serum biochemical analysis. A total of 96 tilapia juveniles were used, exposed to 32mgL for 24, 48, 168, and 360 hours. In the biochemical analysis, a decrease in the total protein with elevated triglyceride levels of the exposed group was observed in relation to the control. The other parameters did not present differences between the exposed and control fish. Sublethal concentrations of thiamethoxam are capable of causing toxicity alterations in Nile tilapia, since the dynamics of some biochemical parameters are influenced by the action of this insecticide.